Changes in space development regarding refuges and migration corridors of European bison in Bieszczady Mountains (European Bison Conservation Newsletter, 2011)
Migrations of animals are an important part of their behavior. The possibility of free movement of individuals is the foundation of lasting and stable functioning of the population. Dispersion and migration affect the distribution, number of animals and spatial structure of the population within the living area. Gene flow connected with migration among populations is difficult, and sometimes impossible because of space building. Isolation leads to decrease of immunity and adaptability to environmental changes. Decision of bison introduction to Bieszczady Mountains was made, among other reasons, with regard to the low population density in this region. Currently similar demographic situation is also observed. Depending of the commune, number of people per square meter is still low, from 5 in Lutowiska to 79 in Zagórz. Nowadays another ”colonization wave” of these areas is noticeable. Space development plans lacking animal migration corridors existence may be threat to bison comfort and free migration possibilities. In Bieszczady Mountains space development takes place through the creation oflocal development plans, often without multifunctional objectives considering at the macro level. The exclusion of certain areas from building plans means land value loss therefore compensations should be state-regulated. Activities regarding migratory corridors creation should be international to succeed in entire Carpathian with the bison colonizing.
Keywords: European bison; Bieszczady mountains; reintroduction